A Low-Cost Chlorophyll Fluorescence Sensor System - Gull, Christopher; Minkov, Minko T.; Pereira, Eduardo Gusmão; Nacif, José Augusto M. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2016)
Chlorophyll fluorescence (CF) yield is a well-known method of measuring plant health. Currently, many solutions exist for measuring CF, but the application methods are complex and costs are high. We propose a solution in which we utilise off-the-shelf components in an affordable package, which is able to measure CF. The prototype that was built demonstrates the ability of discriminating between stressed and non-stressed plants, and shows potential as a low-cost fluorometer. As the focus is less on accuracy and more on relative results and cost, this opens up the possibility of using multiple sensors in a wireless sensor network (WSN). In this paper, we explain the underlying methodology and its relation to known methods, and verify the system in its usefulness as a low-cost CF sensor.